Automatic location of relevant time slices and patterns in both signals and video-movies: real-time and off-line visualization - Vega, J.; Castro, R. (Frontiers in Physics, 2025)
Next generation nuclear fusion devices, (for instance ITER), will generate Pbytes of data. To gain knowledge about the nature of thermonuclear plasmas, an in depth analysis of such massive databases is required. Typically, to get statistical relevance in the study of the plasma properties, particular databases around specific plasma events are created. This means their location not only in discharges but also in the corresponding times. In this respect, visualization tools are essential. Of course, manual location of any relevant phenomenology by means of visual analysis is no longer valid. Instead, automatic software based methods are necessary. These methods have to be applied in both real-time and off-line not only for visualization purposes but also for data access. Candidates for their implementation are machine learning techniques.